THE LECTURERS’ EXPERIENCES ON STUDENTS’ THESIS SUPERVISION - Rahmi Fhonna (Getsempena English Education Journal, 2020)
Many articles regarding thesis assessment and its problems have been published for years. The dynamic of the relationship between the lecturers and their students are highly concerned. This paper, in addition, aims at investigating the lecturers’ experiences while supervising the thesis of students. 5 (five) lecturers from English Department of UIN Ar-Raniry were chosen randomly as the participants for this study. To collect the data, an open-ended interview was designed as an instrument to offer 6 (six) questions to be answered by the participants. The result of the interview showed that different strategies were applied by the participants during the supervision process. Arranging specific time of supervising was employed by each participant in order to discuss more details the thesis written. Students’ writing skill, in this case, was one of the issues highlighted that required specific handling. The result also identified the way of the participants deal with the problems arose; for instance, providing extra time of supervision for the students, asking the students to have peer-reviewed session to proof-read the thesis, and many other strategies. During the consultation period of the thesis, the lecturers believed that they built good communication and relationship with their students, which is very important as the encouragement for the students in completing their theses.